Prevalence of antibiotic resistance in E. coli in leachate - Nurul Syazana, Azman; Nazira, Mahmud; Hajar Fauzan, Ahmad; Mohd Fazli, Farida Asras; Noor Faizul Hadry, Nordin; Nurul Shakila, Khalid; Nurul Azyyati, Sabri (Elsevier Ltd, 2023)
Landfill is one of the common practices for the disposal of municipal solid waste and may include possible contaminants such as antibiotics and heavy metals. The leachate produced from landfill has the potential to become a reservoir of antibiotic residues and heavy metals, leading to the dissemination of antibiotic resistance to the nearby environment. Not only that, enteric bacteria like Escherichia coli (E. coli) may be exposed to these contaminants. E. coli tended to survive in such stressful conditions due to the activation of the stress response. Therefore, this study was conducted to investigate the antibiotic susceptibility of E. coli in leachate. The E. coli was isolated in a landfill in Jabor, Kuantan, Pahang from three sampling points which were garbage hill, leachate pond, and river. The concentration of heavy metals was analyzed using ICP-MS while the antibiotic susceptibility test was performed using the disc diffusion method. Four out of six parameters measured have exceeded the standard permitted range where TSS was 110–580 mg/mL, BOD was 28–176 mg/mL, COD was 447–5100 mg/mL and NH3-N was 9–22 mg/mL. There were five elements (chromium, zinc, copper, manganese, and iron) were detected in leachate where the concentration of iron was the highest (0.158 ± 0.0203–2.287 ± 0.0706 mg/mL) among all metals measured. Besides, the colonies of E. coli were successfully isolated from each sampling point. In this study, all isolated E. coli from garbage hill and leachate pond show resistance towards three antibiotics tested (sulfamethoxazole, tetracycline, and erythromycin). However, isolated E. coli from the river shows intermediate sensitivity to sulfamethoxazole but is resistant to tetracycline and erythromycin. Based on the results, we can conclude that the landfill has the potential to retain pollutants such as TSS, COD, BOD, NH3-N, and antibiotic resistance even though the concentration of heavy metals decreased and meet the standard permitted limit. It shows that the landfill and leachates may act as an important reservoir of heavy metals and antibiotic resistance and potentially affect the environment.